Loss-of-function SLC30A2 mutants are associated with gut dysbiosis and alterations in intestinal gene expression in preterm infants. (31st December 2022) - Kelleher, Shannon L; Alam, Samina; Rivera, Olivia C; Barber-Zucker, Shiran; Zarivach, Raz; Wagatsuma, Takumi; Kambe, Taiho; Soybel, David I; Wright, Justin; Lamendella, Regina
ABSTRACT: Loss of Paneth cell (PC) function is implicated in intestinal dysbiosis, mucosal inflammation, and numerous intestinal disorders, including necrotizing enterocolitis (NEC). Studies in mouse models show that zinc transporter ZnT2 ( SLC30A2 ) is critical for PC function, playing a role in granule formation, secretion, and antimicrobial activity; however, no studies have investigated whether loss of ZnT2 function is associated with dysbiosis, mucosal inflammation, or intestinal dysfunction in humans. SLC30A2 was sequenced in healthy preterm infants (26–37 wks; n = 75), and structural analysis and functional assays determined the impact of mutations. In human stool samples, 16S rRNA sequencing and RNAseq of bacterial and human transcripts were performed. Three ZnT2 variants were common (>5%) in this population: H 346 Q, f = 19%; L 293 R, f = 7%; and a previously identified compound substitution in Exon7, f = 16%). H 346 Q had no effect on ZnT2 function or beta-diversity. Exon7 impaired zinc transport and was associated with a fractured gut microbiome. Analysis of microbial pathways suggested diverse effects on nutrient metabolism, glycan biosynthesis and metabolism, and drug resistance, which were associated with increased expression of host genes involved in tissue remodeling. L 293 R caused profound ZnT2 dysfunction and was associated with overt gut dysbiosis. Microbial pathway analysis suggested effects on nucleotide, amino acid and vitamin metabolism, which were associated with the increased expression of host genes involved in inflammation and immune response. In addition, L 293 R was associated with reduced weight gain in the early postnatal period. This implicates ZnT2 as a novel modulator of mucosal homeostasis in humans and suggests that genetic variants in ZnT2 may affect the risk of mucosal inflammation and intestinal disease.